Compact internal sensing phase locking system for coherent combining of fiber laser array. (April 2022) - Long, Jinhu; Chang, Hongxiang; Zhang, Yuqiu; Hou, Tianyue; Chang, Qi; Su, Rongtao; Ma, Yanxing; Ma, Pengfei; Zhou, Pu
Highlights: In the internal sensing technique, the large-aperture beam splitters and lens are no longer needed for phase locking. The internal sensing phase-locking system is compatible with fiber laser array with large cross-section. The internal phase noises and external phase differences can be compensated by the phaselocking system, respectively. This technique is based on spatial configuration, it can be further used in high-power coherent beam combining systems. Abstract: A compact internal sensing phase locking system for coherent combining of large aperture fiber laser beams is demonstrated in this paper. Herein, the phase noises in the laser channels are detected and compensated before the lasers form a large cross-section laser array. Therefore, the large aperture beam splitters and lens are no longer needed for phase locking, and the phase-locking system can be more compact, especially for the coherent laser array with large cross-section. We built a 7-channel fiber laser array to experimentally verify the feasibility of this technique. The phase deviation was less than λ/31 RMS, and the visibility of far-field interference pattern of the combined beam was ∼96.3%. This technique can be used in high-power coherent beam combining system with the large aperture laser beams.